Leitura prévia e performance à primeira vista no ensino de piano complementar: implicações e estratégias pedagógicas a partir do Modelo C(L) A(S)P de SWANWICK - Ana Consuelo Ramos (2005)
One had better set out to focus on the importance to the piano process initiation, aiming at pedagogical principles and strategies which lead to a score reading, in a gradual, systematic and contextualized way. A broader view has been granted to the piano. Such a view surpasses the performance, also featuring it as a complimentary and musicalizing instrument to the musicians development. By means of a research-action, carried out among students of the Bachelor of Music Course Majoring in Singing at the School of Music of the University of Minas Gerais State (UEMG), one tries to check the relevance to the minute observation of the score before its playing the previous reading. The procedure upheld by musical experiments with no score is featured by the visual analysis of the musical content, which makes it possible an internalized score hearing, apart from counting a historical contextualization in. The previous reading stands for a pedagogical strategy used as a preliminary pathway to get to the performance and to what is regularly known as sight-reading. In this paper such conceptual distinctions have been bounded so as to determine broaching procedures and score accomplishment, interrelating other terminologies such as first performance, sight-playing and sight-performance.As the chief theoretical grounding, the Model C(L)A(S)P, by Swanwick (1979) has been displayed. That one supports itself on the statements acquired from interviews to professors and also from oral and written assertions provided by the pupils engaged in the research.The conclusion comprises discussions connected with the methodological procedure, used in this course of study the researchaction and with the subject itself, by taking into account: pedagogical ploys, which include performances without a score music stemming from imitation, learning by heart, oral musical work and improvisations linked to the habit of tactics, such as previous reading are likely to go a long way to optimize the musical reading systems, to broaden the understanding of the work and also to aim more refined sight-performances.